Do stress and anxiety lead to belief in conspiracy theories? [version 1; peer review: 5 approved] - Matt N. Williams; Nick Fox (Routledge Open Research)
Conspiracies happen, and some conspiracy theories are warranted by evidence. Nevertheless, a non-trivial proportion of the public express belief in conspiracy theories that are not warranted by evidence. Psychological research has therefore investigated the motives that might lead someone to believe a conspiracy theory even where the available evidence for the theory is weak. Two potential causes that have been proposed in the literature and embedded in theorising are psychological stress and anxiety. Prior studies have provided some evidence that stress and anxiety are positively correlated with belief in conspiracy theories, but it remains unclear whether this apparent effect might be accounted for by plausible confounding variables. Furthermore, there have been few preregistered examinations of the proposed effects of stress and anxiety, rendering it unclear to what degree this proposition has yet been subjected to a severe test. In two preregistered cross-sectional survey studies, we tested whether higher perceived stress and anxiety significantly predicted belief in conspiracy theories while controlling for plausible confounding variables (age, education, subjective social status, and political orientation). We analysed data using structural equation models, allowing measurement error to be explicitly modelled and accounted for. In Study 1 (N =502), a cross-sectional survey of Australasian participants indicated that perceived stress and anxiety did not have significant estimated effects on belief in conspiracy theories. In Study 2 (N =1020), a cross-sectional survey of US participants showed a small significant positive effect of perceived stress, but not anxiety, on belief in conspiracy theories. The present results provide very tentative evidence for an effect of perceived stress on belief in conspiracy theories. However, it is increasingly evident that this effect, if it exists at all, is not large.